Antioxidant and Hepatoprotective Activities of Polysaccharides from Spent Mushroom Substrates (Laetiporus sulphureus) in Acute Alcohol-Induced Mice. (21st December 2017) - Zhao, Huajie; Lan, Yufei; Liu, Hui; Zhu, Yongfa; Liu, Weiru; Zhang, Jianjun; Jia, Le
Abstract : In order to contribute to the exploitation and utilization of spent mushroom substrates (SMS) of Laetiporus sulphureus, hot-water-extractable polysaccharides (H-SMPS) and enzymatic-extractable polysaccharides (E-SMPS) were successfully isolated from SMS of L. sulphureus . Both H-SMPS and E-SMPS were found to have high reducing power and potential scavenging activities against hydroxyl, DPPH, and superoxide anion radicals. In vivo assays showed that the administration of H-SMPS and E-SMPS has potential hepatoprotective effects against alcohol-induced alcoholic liver disease (ALD), possibly brought about by improving liver function, increasing antioxidant status, and reducing lipid peroxidation. Furthermore, monosaccharide composition analysis showed that fucose may play a vital role in guaranteeing stronger hepatoprotection. These results may provide references for the exploitation of the SMS of L. sulphureus as a source of H-SMPS and E-SMPS, which in turn can be used as functional foods or natural drugs for the prevention of ALD and other liver diseases.